Animal genetic resources research and development in Africa - Rege, J.E.O. (Southern African Development Community, 2001)
The first part of this paper, the introduction, summarises ILRI's mandate and mission. Then the paper outlines the animal genetic resources (ANGRs) work at ILRI; including livestock genetics and Genomics, AnGRs current content; characterisation (Assessment of genetic diversity in AnGRs); DAGRIS (Domestic AnGRs Information System); capacity building for sustainable AnGrs management; economic valuation of AnGRs; breeding strategies for sustainable use of AnGRs in low- to medium - input systems; and AnGRs work by NARS. The rest of the paper outlines the SADC AnGRs project; AnGRs in Africa; and indigenous AnGRs.